Analisis Pengaruh Diskon Harga, Kualitas Produk, dan Promosi terhadap Pembelian Impulsif di Tiktok Shop: Studi Pengguna Aktif di Kabupaten Buleleng - Saragih, Merry Artianni; Suwendra, I Wayan (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the influence of price discounts, product quality, and promotions on TikTok Shop with a case study of active users in Buleleng Regency. The growing phenomenon of online shopping, especially through TikTok Shop, has given rise to spontaneous or impulsive buying behavior. This study employs a quantitative approach using a survey method, with data collected through a questionnaire distributed to 100 respondents selected using purposive sampling. The independent variables in this study are price discounts, product quality, and promotions, while the dependent variable is impulsive buying. The collected data were analyzed using multiple linear regression through SPSS version 25. The results of the study indicate that price discounts, product quality, and promotions simultaneously have a significant effect on impulsive buying. Partially, these three variables also prove to have a significant positive effect. Price discounts are the most dominant factor in driving spontaneous purchasing decisions, followed by promotions and product quality. This indicates that consumers are more likely to make unplanned purchases when exposed to attractive, urgent offers, especially on interactive platforms such as TikTok Shop. The conclusion of this study is that marketing strategies that combine price discounts, product quality, and attractive and interactive promotions can increase the tendency for impulsive buying. These findings are expected to serve as a reference for businesses in designing attractive marketing strategies to increase the appeal of impulsive buying.